Effects of Print Exposure on an Online Lexical Decision Task: A Direct Replication Using a Web-Based Experimental Procedure - Kim, Dahyeon; Lowder, Matthew W.; Choi, Wonil (Frontiers in Psychology, 2021)
Due to the global pandemic, behavioral sciences including psychology that have traditionally relied on face-to-face data collection methods are facing a crisis. Given these circumstances, the present study was designed as a web-based replication of the findings reported in Lee, Seong, Choi, and Lowder (2019) on the relationship between print exposure measured by the Korean Author Recognition Test (KART) and online measures of word processing using the lexical decision task and offline measures of language ability. We used the PsychoPy3 and Pavlovia platform in which participants were presented with a series of tasks in an entirely web-based environment. We found that scores on the KART were correlated with scores on a measure of language skills as well as self-reported reading habits. In addition, KART scores modulated the word frequency effect in the lexical decision task such that participants with higher KART scores tended to have smaller frequency effects. These results were highly consistent with previous lab-based studies including Lee et al., indicating that web-based experimental procedures are a viable alternative to lab-based face-to-face experiments.